On convex combinations of Hurwitz polynomials - Gregor, Jiři; Tišer, Jaroslav (Zielona Góra: Uniwersytet Zielonogórski)
The zero set of a convex hull of two polynomials is investigated with special attention to the class of Hurwitz polynomials. New necessary and sufficient conditions are given for a convex hull of these polynomials to belong to the same class. An algorithm of construction of Hurwitz interval polynomials containing a given Hurwitz polynomial is formulated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka